ANALISIS FAKTOR YANG MEMPENGARUHI KEPATUHAN MEMBAYAR PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN SRAGEN - Nur Endah Fajar hidayah; Erik Muhammad Hanafi (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study to analyze factors influencing taxpayer compliance in paying Rural and Urban Land and Building Tax (PBB-P2) in Sragen Regency. Tax compliance is a crucial issue in state revenue, and understanding the factors that influence it is crucial for designing effective tax policies. The independent variables studied are taxpayer awareness, tax socialization, and the tax system, with PBB-P2 taxpayer compliance as the dependent variable. Data were collected from taxpayers in Sragen Regency and analyzed using multiple linear regression methods.   The results of the regression test indicate that not all hypothesized factors have a significant influence on tax compliance. Partially, the variables of taxpayer awareness and the tax system were shown to have a positive and significant influence on compliance with PBB-P2 payments. This indicates that the higher the taxpayer awareness and the better the tax system implemented, the higher the level of taxpayer compliance. Conversely, the variable of tax socialization was found to have no significant effect on taxpayer compliance. This finding suggests that the existing socialization program may not be effective or needs to be re-evaluated to achieve a more tangible impact.   Based on these findings, this study recommends that the local government and tax authorities in Sragen Regency focus more on increasing taxpayer awareness and continuously improving the tax system. Although the socialization program was not statistically significant, it is recommended to review the socialization strategy to make it more targeted and relevant to taxpayer needs. This is expected to improve taxpayer compliance with PBB-P2, which will ultimately have a positive impact on regional revenue.